ISSUES AND CHALLENGES OF THE PARAGUAYAN EDUCATIONAL SYSTEM´S MANAGEMENT BASED ON CAPACITIES FOR THE SECONDARY LEVEL. A COMPARATIVE CASE STUDY WITH THE CURRICULUM OF QUEBEC - Martinez David; Diah Susanti; Meng Huy Teang (Science Education, Institut Agama Islam Negeri Ponorogo, 2022)
This study seeks to generate knowledge and scientific result based on a comparative case study of Canadian (Quebec) educational management for the improvement of the education quality in Paraguay. Also, this research will provide a basis for future studies that can aim at raising the quality of work with other countries to face educational projects in a short, medium and long term. It will provide data to the Government staff for making future decisions. This study is designed with respect to the qualitative research method, the theoretical research and comparative case study. The responses of the interview are essential to compare with the literature review and then make conclusions. These conclusions aim to show the possibility of implementing new strategies of educational management in Paraguay. In order to collect data two professionals in the field of education system from Paraguay and Canada (province of Quebec) will participate in this study by giving their knowledge, opinion and experiences applying a questionnaire. The overall finding of the study, based on these interviewee’s experiences and the literature review, indicates that the educational management based on capacities improvement has a positive impact on society in terms of inculcating new abilities, knowledge, and values among students to face real needs and issues of the real life. In this respect, this paper provides beneficial information explaining that teachers’ work, supported by an innovative, dynamic and participatory educational management, increases the quality of education of students